Technocrats and the Politics of Drought and Development in Twentieth-Century Brazil - Buckley, Eve E. (The University of North Carolina Press, 2023)
Eve E. Buckley’s study of twentieth-century Brazil examines the nation’s hard social realities through the history of science, focusing on the use of technology and engineering as vexed instruments of reform and economic development. Nowhere was the tension between technocratic optimism and entrenched inequality more evident than in the drought-ridden Northeast sertão, plagued by chronic poverty, recurrent famine, and mass migrations. Buckley reveals how the physicians, engineers, agronomists, and mid-level technocrats working for federal agencies to combat drought were pressured by politicians to seek out a technological magic bullet that would both end poverty and obviate the need for land redistribution to redress long-standing injustices.